Instrument Readiness Analysis of Technology-Based Businesses - Muhammad Luthfi Hamzah; Astri Ayu Purwati (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Digital technology is currently highly developed in all fields. The development of this technology certainly has a big impact on the world of business and industry. This study tries to prove the effect of instrument readiness in developing technopreneurship abilities in students. The readiness instrument variables used are Capital Thourgh, Information and Social Network. The study was conducted on 150 students who have technology-based businesses (technopreneurs) as samples. The data analysis technique used is the structural equation model with the help of Smart PLS. The results showed that Capital Through did not have a significant effect on technopreneurship, but Information and Social Networks had a positive influence on technopreneurship. In addition, the Social Network is able to encourage a technopreneur to make it easier to obtain information related to business development.